Field information of spring-planted rape herbicidal defense with preparations of Ltd. "FMRus" in LLC "Start" - Bezgodov A. V., Kovalev A. N., Kokovin I. N. (Scientific studies: from theory to practice, 2016)
In field experiments it was tasked to pick an effective system oto protect of spring rape crops from weeds, allowing to receive stable high productivity from commodity rapeseeds. Evaluation of productivity and suitability for the cultivation of oilseeds on commodity and seeds in the region of the Middle Urals in nine cases of intensification of the use of plant protection products in order to evaluate and use in a production environment. It was found that the studied drugs have unequal impact on the growth and development of plants and yield formation.
Keywords: технология; алгоритм; урожайность; сельское хозяйство; семена; agriculture; technology; algorithm; средства защиты растений; yield; seeds; plant protection products; рапс; бутонизация; почвенный гербицид; баковая смесь; Галактик Супер; Дифилайн; Премьер 300; густота стояния растений; десикация; rape; budding; soil herbicide tank-mix; Galactic Super Difilayn; Prime 300; plant density; desiccation